Catalytic application of layered double hydroxides and fluoroperovskites in glycerol oligomerization - Barros, Fernando José Soares (2019)
Glycerol has become an important feedstock for industries due to its low price, high availability and the possibility of producing several value-added compounds. Its oligomers, diglycerol and triglycerol, find applications in polymers, foods and cosmetics. In this study, layered double hydroxides (LDHs) and fluoroperovskites, both containing Mg/Al, Zn/Al and Co/Al were obtained by coprecipitation and used as catalysts in glycerol oligomerization. Modification of LDHs by rehydration via ultrasound and mechanical agitation was evaluated. Catalysts using the above-mentioned materials as support for cobalt(II) acetylacetonate were prepared as well. The solids were characterized by inductively coupled plasma optical emission spectrometry (ICP-OES), X-ray diffraction, Fourier transform infrared spectroscopy, thermogravimetric analysis (TGA), textural properties by nitrogen adsorption, transmission electron microscopy (TEM), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). Basicity was studied by temperature-programmed desorption of CO2 and irreversible adsorption of strong acids measured with ultraviolet-visible spectroscopy. The influence of catalyst loading, reaction time and temperature were evaluated. The products were analyzed by gas chromatography and the occurrence of leaching was verified by ICP-OES. The spent catalysts were studied by TGA and XPS. For Mg/Al LDH, a modification strategy was developed with the addition of acetic acid. The best performance achieved in this group led to 64% of glycerol conversion (XGly), 37% of diglycerol selectivity (Sdi) and 4 reaction cycles (reaction with 4% cat., at 240 °C for 8 hours). For Zn/Al group, the use of fluoroperovskite was more effective, leading to 68% of XGly, 27% Sdi and 4 cycles (4% cat., at 230 °C and 18 hours). Among the materials impregnated with cobalt(II) acetylacetonate, the Mg/Al LDH support showed better performance with 68% XGly, 27% Sdi and 4 cycles (4% cat., 240 ° C and 8 hours). Catalyst deactivation was related to the harsh reaction conditions, that led to the loss of active species or their blockage by impurities. Nevertheless, the several strategies adopted showed that it is viable to produce glycerol oligomers with heterogeneous catalysis.